Constructing novel double‐bond‐containing well‐defined amphiphilic graft copolymers via successive Ni‐catalyzed living coordination polymerization and SET‐LRP. Issue 9 (7th February 2013) - Li, Yongjun; Lu, Guolin; Dai, Bin; Xu, Caixia; Huang, Xiaoyu
Abstract A series of polyallene‐based well‐defined amphiphilic graft copolymers, poly(6‐methyl‐1, 2‐heptadiene‐4‐ol)‐g‐poly(2‐(diethylamino)ethyl methacrylate) (PMHDO‐g‐PDEAEMA), was synthesized through the grafting‐from technique. First, double‐bond‐containing PMHDO backbone bearing pendant hydroxyls was prepared via [(η3‐allyl)NiOCOCF3]2‐initiated living coordination polymerization of 6‐methyl‐1, 2‐heptadiene‐4‐ol (MHDO). The pendant hydroxyls in the homopolymer were then reacted with 2‐chloropropionyl chloride to give PMHDO‐Cl macroinitiator. Finally, hydrophilic PDEAEMA side chains were formed by single electron transfer‐living radical polymerization (SET‐LRP) of 2‐(diethylamino)ethyl methacrylate (DEAEMA) in THF/H2O initiated by the macroinitiator using CuCl/Me6TREN as catalytic system to afford PMHDO‐g‐PDEAEMA graft copolymers. The narrow molecular weight distributions (Mw/Mn ≤ 1.35) and kinetics experiment showed the controllability of SET‐LRP graft copolymerization of DEAEMA. The critical micelle concentration (cmc) of PMHDO‐g‐PDEAEMA amphiphilic graft copolymer in aqueous media was determined by fluorescence probe technique and the relationships between cmc and pH or salinity were also investigated. Micellar morphologies were preliminarily explored using transmission electron microscopy. © 2013 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem, 2013